2021
DOI: 10.1002/lio2.599
|View full text |Cite
|
Sign up to set email alerts
|

Does stapedotomy improve high frequency conductive hearing?

Abstract: Objectives Stapedotomy is performed to address conductive hearing deficits. While hearing thresholds reliably improve at low frequencies (LF), conductive outcomes at high frequencies (HF) are less reliable and have not been well described. Herein, we evaluate post‐operative HF air‐bone gap (ABG) changes and measure HF air conduction (AC) thresholds changes as a function of frequency. Methods Retrospective review of patients who underwent primary stapedotomy with incus wire piston prosthesis between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There were no significant differences among BC-LF, BC-MF, and BC-HF in the MSS group. Similarly, Roychowdhury et al found that ABG-LF improved significantly more than ABG-LF after stapedotomy (12), and presented a simple linear regression model demonstrating that ΔAC (y) decreases as the frequency (x) increases [y=-0.003853x+34.76 (R 2 =0.951), P<0.001], and indicated that there was no significant difference between preoperative and postoperative thresholds at 8 kHz. One hypothesis could be that the surgical wound is on the vestibular window and HF soundwaves cause vibrations only on the basement membrane around the vestibular window, therefore LF and MF data have better post-stapedotomy outcomes than HF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There were no significant differences among BC-LF, BC-MF, and BC-HF in the MSS group. Similarly, Roychowdhury et al found that ABG-LF improved significantly more than ABG-LF after stapedotomy (12), and presented a simple linear regression model demonstrating that ΔAC (y) decreases as the frequency (x) increases [y=-0.003853x+34.76 (R 2 =0.951), P<0.001], and indicated that there was no significant difference between preoperative and postoperative thresholds at 8 kHz. One hypothesis could be that the surgical wound is on the vestibular window and HF soundwaves cause vibrations only on the basement membrane around the vestibular window, therefore LF and MF data have better post-stapedotomy outcomes than HF.…”
Section: Discussionmentioning
confidence: 96%
“…Shiao et al and Babighian et al demonstrated significant improvement in average air conduction (AC) and air-bone gap (ABG) (P<0.001) and no difference in bone conduction (BC) after surgery were reported in their cases (10,11). In their study, Roychowdhury et al reported that low-frequency (LF) AC and ABG improved significantly more after stapedotomy than high-frequency (HF) AC and ABG (12).…”
Section: Introductionmentioning
confidence: 95%